Efek Pemberian Ketamin Dosis 0,5 Mg/Kgbb Terhadap Onset Blokade Neuromuskular Oleh Atrakurium - Al-Hilal, Said Rival; Sarosa H, Pandit; Widodo, Untung (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2018)
Background. Atracurium is a nondepolarizing muscle relaxant agent. The onset of this drug is slower than succinylcholine thus limiting its use. Various attempts had been made to accelerate the onset of the nondepolarizing muscle relaxants. Various reports suggest that ketamine is associated with a better intubation conditions. Aims. The aim of this study was to determine the effect of ketamine 0.5 mg.kg-1 on neuromuscular blockade onset of atracurium. Method. The method was a Randomized Controlled Trial (RCT) with double blinding. Eighty adult patients aged 18-65 years with physical status according to class I and II of ASA classification who were undergoing elective surgery under general anesthesia in November 2016 up to January 2017, patients who met the inclusion and exclusion criteria were randomly divided into two groups: K (Ketamine ) and group S (Saline Control). Group K was given ketamine 0.5 mg.kg-1 while the S was given Saline. Eight patients were otherwise drop out because of tool’s error. The Onset of atracurium was measured by using a Train of Four. Result. The results of this study were the onset of neuromuscular blockade by atracurium in the ketamine group significantly faster (160.500 ± 58.956 seconds vs 288.750 ± 135.038 seconds; p = 0.001). Hemodynamic 8 changes (∆MAP : 6,500±7,965 mmHg vs 10,750±14,655 mmHg & ∆pulse rate : 3,737±11,700 x/minute vs 4,333±12,254 x/min) was not statistically significant (p = 0.123 and p = 0.831). Conclusion: The administration of ketamine 0.5 mgkg-1 accelerate the onset of neuromuscular blockade of atracurium.